Factors Affecting Tax Aggressiveness In Plantation Companies Listed 2014-2017: Faktor-Faktor Yang Mempengaruhi Agresivitas Pajak Pada Perusahaan Perkebunan Yang Terdaftar Tahun 2014-2017 - Azmi, Fika; Ramadhani, Linda (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to obtain empirical evidence about the factors that influence tax aggressiveness. The independent variables in this study are Corporate governance, Inventory Intensity and Fixed Assets Intensity. The sample in this study were plantation sector companies listed on the Indonesia Stock Exchange in 2014-2017. The sampling technique used purposive sampling method, and obtained data as many as 32 samples. The data analysis technique uses multiple linear regression analysis. The results showed that independent commissioners and inventory intensity did not affect to tax aggressiveness, institutional ownership had a positive effect to tax aggressiveness and managerial ownership and the intensity of fixed assets negatively affected to tax aggressiveness.